Hopanes and Polyaromatic Hydrocarbons from 21 2t Oil as Molecular Markers for Detecting the Sources of Hydrocarbon Pollution - Wong, Yoon Lee (2005)
Rapid growth of population, urbanization and industrialization in Malaysia led to sharp increase in numbers of motor vehicles. Therefore motor oils are potential landbased sources that contributed to hydrocarbon pollution in Malaysia. Two-cycle lubricating oil (2T oil) is a lubricating base oil specially used in two-stroke motorcycle engines. Lubricating base oils are complex mixtures of hydrocarbons. This study focused on alkanes, hopanes and PAHs in 2T oil due to their importance as molecular markers and their combination would be a powerful tool to distinguish input, sources and transport pathway of hydrocarbon pollution. The objective of this study is to analyze alkanes, hopanes and PAHs from 2T oil. Alkanes, hopanes and PAHs fiom 2T oil were used as molecular markers and were applied for detectmg the sources of hydrocarbon pollution and the transport pathway of the 2T oil. Three kinds of commonly use fresh 2T oil samples were purchased fiom local market. Used 2T oil sample was collected with pre-cleaned cotton buds from twostroke motorcycles tail pipes at Central Parlung of Universiti Putra Malaysia. The cotton buds were rinsed with 3:l HexfDCM. The extract was fractionated and analyzed for PAHs, Hopanes and alkanes by gas chromatography mass spectrometry (GC-MS). The result indicates that used 2T oil contained much higher concentration of PAHs than fiesh 2T oil due to formation of PAHs in concentration during hlgh temperature combustion in the engine (Rafael, 1989). Application of the source identifiers, UCM, PrPh, CPI, C29/C30E, C3*< 35/C30, MPIP and WL-PAH suggested that hydrocarbon from fresh and used 2T oil both were contributing to the street dust and air particulate in some level of contamination through the exhaust of two-stroke motorcycles. Combination of the alkanes, hopanes and PAHs fingerprints comparison among fresh and used 2T oil, river, inshore, offshore, street dust and air particulate showed that both hydrocarbons fiom fresh and used 2T oil were sipficant in coastal environment of Malaysia and they had been potentially transported via street dust and air particulate. PAHs fiom 2T oil might be discharged to river and inshore coastal zone of Malaysia through street dust and air particulate via lateral and vertical transportation.